Pelatihan Bahasa Inggris Untuk Masyarakat Hinterland Dalam Pengembangan Kampung Wisata Pasir Panjang - Arta Uly Siahaan; Condra Antoni; Satria Bayu Aji; Yosi Handayani; Agus Fatulloh; Mira Chandra Kirana; Nelmiawati Nelmiawati; Rina Yulius; Maidel Fani; Festy Winda Sari; Riki Riki; Ardiman Firmanda; Roza Puspita; Muhammad Idris (Pusat P2M Politeknik Negeri Batam, 2019)
Nowadays, English should be mastered by all level of people and for all ages namely for children, teenagers or adults. There is a special challenge for improving the ability especially for hinterland society. For Rempang Cate citizen which is one of tourism destination in Batam, it is still far from the expectation. The idea of this community service is to improve the communication as the tourist destination host especially English for tourism. Finally, by giving this training to them, it is expected that they are able to attract more tourst to visit this place. The method of this community service is by giving training to three levels of class by providing material related to simple conversation fo tourism. Based on general result of questionnaire, everything ran well and no obstacles and difficulties happened to organize this training. It was very helpful to improve the readiness of the society to welcome the tourist.